ANALISIS PENGARUH ROA, FDR, CAPITAL, CAR TERHADAP RATE OF RETURN DEPOSITO MUDHARABAH PADA PT BANK SYARIAH MANDIRI. - Susanto, Eko (Universitas Muhammadiyah Prof DR HAMKA, 2019)
Analysis of the effect Return On Asset, Financial to Deposit Ratio, Capital Adequacy Ratio on Rate Of Return Deposits in Mandiri Islamic Banking Mudharabah, In Data Collection, This Research use secondary data obtained from statistic Mandiri Islamic Bank 2012-2015 and issued by the bank of Indonesia. he type of research used in this research is quantitative research, research which emphasizes on testing theories through the variables research in numbers and performing data analysis with statistical procedures or mathematical capital. The object of the research used in this study is PT. Bank Syariah Mandiri by using secondary data in the form of a Keuanagan publication reports on everything from January 2012 to December 2015. So it can be inferred that the variable ROA, FDR, and CAR together or simultaneous has significant effects against a Rate of Return of deposits Mudharabah 1 month. Thus the ROA, the FDR, and the CAR partially have significant influence and effect on Rate of Return (ROR) Mudharabah Deposits. Keywords; ROR Deposito Mudharabah, ROA, FDR, and CAR.